Using audiovisual material to teach refusals from a discursive perspective: a research-based proposal - Usó Juan, Esther; Martínez Flor, Alicia (Complutense Journal of English Studies, 2022)
Refusals are complex face-threatening speech acts whose appropriate performance requires not only lengthy sequences of negotiation and cooperative achievements, but also face-saving strategies to accommodate the disruptive nature of the act (Gass & Houck 1999). Also, since they have a face threatening nature, they are subject to cultural variations. Consequently, care must be taken in the choice of refusal strategies. On that account, this paper first describes the speech act of refusal and reviews findings of empirical interventional studies on this speech act, with particular interest in understanding their methodological choices. Then, it presents the benefits of using audiovisual material for teaching pragmatics in a foreign or a second language instructional context. Finally, relying on excerpts from TV series, an instructional method for teaching refusals at the discourse level is presented. All the designed activities are built upon research-based recommendations for teaching refusals in hopes to provide teachers with resources and ideas for including pragmatics into their language courses.